The Use of A Geographically Weighted Regression Model to Analyze Predictors of The Rice Supply in Bojonegoro - Nurdiansyah, Denny; Ma'ady, Mochamad Nizar Palefi; Kartini, Alif Yuanita; Yuliana, Ummi Agustin (Universitas Islam Lamongan, 2024)
The research goal would be to understand all potential influences on the amount of rice available within every sub-district in the Bojonegoro district. Geographically weighted regression (GWR), a technique used for this study, uses kernels: adaptive bisquare, fixed bisquare, adaptive gaussian, and fixed gaussian. The state office for food security and farming inside the Bojonegoro district provided secondary statistics for the 2018 year that included information on the population, the harvested area, the rice production, and the rice supply. The outcomes from the kernel-fixed gaussian elected model using AIC minimum criteria for the GWR model. The implementation's conclusion is due to the impact of variety in locations. The next research recommendation is a time-series spatial study of the rice problem.